(untitled) (Journal of Partial Differential Equations, 2014)
" This paper presents the wavelet collocation methods for the numerical approximation of swing options for natural gas storage in a mean reverting market. The model is characterized by the Hamilton-Jacobi-Bellman (HJB) equations which only have the viscosity solution due to the irregularity of the swing option. The differential operator is formulated exactly and efficiently in the second generation interpolating wavelet setting. The convergence and stability of the numerical scheme are studied in the framework of viscosity solution theory. Numerical experiments demonstrate the accuracy and computational efficiency of the methods."